2018
DOI: 10.14499/indonesianjpharm29iss2pp86
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ethanolic Extract Tempuyung Leaf (Sonchus arvensis L.) in Gentamicin-induced Acute Tubular Necrosis on Wistar Rats

Abstract: Acute tubular necrosis (ATN) is the most common histopathologic findings of acute kidney injury (AKI). AKI is marked by the decrement of glomerular filtration rate, causing waste metabolism retention (creatinine). Gentamicin is used as it is the most common nephrotoxic agent in inducing ATN. Tempuyung (Sonchus arvensis L.) has been used in folklore medicine to ameliorate kidney problems as it contains antioxidants, two of which are flavonoid and phenolic acid. Yet, these active substances' benefit on gentamici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Decreased serum urea and creatinine levels revealed an improvement in kidney function of the test animals [30][31][32]. These findings are in line with the report of Imelda et al showed that Sonchus arvensis L. 100 and 200 mg/kg b.w reduced serum urea and creatinine levels after administration of Sonchus arvensis L. extract and gentamicin for ten days, simultaneously [10,33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Decreased serum urea and creatinine levels revealed an improvement in kidney function of the test animals [30][31][32]. These findings are in line with the report of Imelda et al showed that Sonchus arvensis L. 100 and 200 mg/kg b.w reduced serum urea and creatinine levels after administration of Sonchus arvensis L. extract and gentamicin for ten days, simultaneously [10,33].…”
Section: Discussionsupporting
confidence: 89%
“…Sonchus arvensis L. has been shown to have a diuretic effect in rats that have induced hyperuricemia [9]. Sonchus arvensis L. 100 mg/kg b.w have been shown to decrease serum creatinine levels in rat kidney failure induced by gentamicin [10]. It also has antioxidant activity against 2,2diphenyl-1-picrylhydrazyl (DPPH) free radicals, 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) ABTS, OH, and superoxide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, blood was collected from the experimental mice to determine the nephroprotective, hepatoprotective, and immunomodulatory activities after 7 days of treatment with ethyl acetate extract of S. arvensis L. Many studies have reported that S. arvensis L. extracts exhibited antioxidant [25], hepatoprotective [13], nephroprotective [42], and immunomodulatory [43] activities. The present study was conducted to assess the effect of an ethyl acetate extract of S. arvensis L. against P. berghei infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…P. berghei parasites will infect erythrocytes and activate cytokines of phagocytic cells and endothelial cells to produce TNF-α, IL-10, IFN-γ, and free radicals (ROI, ROS, and NO). Free Wahyuni et al BMC Complementary Medicine and Therapies (2023) 23:47 radicals are molecules with one unpaired electron in their outer orbit which makes the molecule unstable [42]. Free radicals can cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation